AKUNTABILITAS PENYELENGGARAAN PEMERINTAH DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) (Studi Alokasi Dana Desa Tahun Anggaran 2015 Di Desa Kerepkidul Kecamatan Bagor Kabupaten Nganjuk) - Supheni, Indrian (STIE PGRI Dewantara Jombang, 2016)
abstractThis research describes and analyzes accountability in managing Budget management of the village (APBDes) in the village government of Kerepkidul Bagor districts Nganjuk regency for Village Fund Allocation (ADD). The research method used is qualitative research, including the type critical. The sources of this study consisted of the headman of Kerepkidul, village secretary, village treasurer, event organizer, and also the chief of BPD and the members of BPD. The collecting data technics used are interview, observation, and document. The data analysis is done with collecting the data, reducing data, interpretation, and taking a conclusion, verification and reflection.The results of this study indicate KerepKidul Village Government Bagor districts Nganjuk regency has implemented the application of the principle of accountability in the management of APBDes fiscal year 2015. The village government of Kerepkidul has proven its commitment or responsibility with how to obey and follow the stages as well as the applicable provisions in accordance with regulations issued by the Nganjuk regency. But in implementing there still found it the problem is for the exceed percentage. But in practicing they found the problem that the large percentage amount which is a little more than is specified. It is expected for future implementation, the village government of Kerepkidul Bagor districts Nganjuk regency can implement the management of Village Fund Allocation (ADD) based on existing regulations as a whole.Keywords: Accountability, Village government, management of the village budget (APBDes), Village Fund Allocation (ADD)Â abstrakPenelitian ini mendeskripsikan dan menganalisis akuntabilitas dalam pengelolaan APBDes di pemerintahan Desa Kerepkidul Kecamatan Bagor Kabupaten Nganjuk pada Alokasi Dana Desa (ADD). Metode Penelitian yang diggunakan adalah penelitian kualitatif yang termasuk dalam jenis Critical. Adapun narasumber penelitian ini terdiri dari Kepala Desa Kerepkidul, Sekretaris Desa, Bendahara Desa, Pelaksana Kegiatan, serta Ketua BPD dan Anggota BPD. Teknik pengumpulan data yang digunakan berupa wawancara, observasi, serta dokumen. Analisis data dilakukan dengan pengumpulan data, reduksi data, interpretasi, dan penarikan simpulan, verifikasi, dan refleksi.Hasil penelitian ini menunjukkan Pemerintah Desa Kerepkidul Kecamatan Bagor Kabupaten Nganjuk sudah melaksanakan penerapan prinsip-prinsip akuntabilitas pada pengelolaan APBDes tahun anggaran 2015. Pemerintah Desa Kerepkidul telah membuktikan komitmennya atau tanggungjawabnya dengan cara mematuhi dan mengikuti tahapan serta ketentuan yang berlaku sesuai dengan Peraturan yang telah dikeluarkan oleh Bupati Nganjuk. Namun dalam penerapannya masih ditemukan permasalahan yakni pada besar jumlah persentase yang sedikit melebihi dari yang ditetapkan. Diharapkan untuk pelaksanaan kedepannya, pemerintah Desa Kerepkidul Kecamatan Bagor Kabupaten Nganjuk bisa melaksanakan pengelolaan ADD berdasarkan peraturan yang ada secara keseluruhan.Kata Kunci: Akuntabilitas, Pemerintah Desa, APBDes, ADD.